Modelling and control for longitudinal dynamics of aircraft system / Nurbaiti Wahid, Mohd Aldrin Ali & Nordiana Mukahar - Wahid, Nurbaiti; Ali, Mohd Aldrin; Mukahar, Nordiana (2012)
Today’s aircraft designs rely heavily on automatic control system to monitor and control many of aircraft’s subsystem. Development of automatic control system has played an important role in the growth of civil and military aviation. One of the major problems of flight control system is due to the combination of nonlinear dynamics, modelling uncertainties and parameter variation in characterizing an aircraft and its operating environment. In recent years, many researches find that the uncertainty associated with modelling, and the complexity of the nonlinear phenomena present the main challenges in developing flight control systems. Thereby, this research is attempted to study the advanced control strategies required to address the complex nonlinear longitudinal dynamic characteristics of such aircraft. In longitudinal control, it involved pitch axis of an aircraft system and the elevators controls the longitudinal motion. Specifically, the research objective are i) to study the complex dynamics behavior of aircraft system and develop the suitable mathematical model for aircraft longitudinal control and ii) to identify the suitable model parameters in modelling of longitudinal controller of aircraft system and iii) to evaluate and compare the performance of several controllers including modern and advanced control for aircraft longitudinal dynamic. This research is conducted to model the appropriate control schemes for longitudinal control, in order to study the complex dynamics behavior of aircraft system. It begin by define the model for longitudinal controller to describe dynamics of system in a set of differential equation. Several control strategies including modern and advanced control will be developed and performance of the controllers will be analyzed. The model will be validated through simulation using MATLAB. At the end of this research it is expected, to achieve an accurate model representing the actual system behavior. Performance comparison between several control strategies for aircraft longitudinal control also will be reported.